Echocardiographic evaluation of diastolic dysfunction in type 2 diabetes mellitus without cardiac manifestations in rural hospital - Khade, Sachinkumar K; Kumar, Sudeep; Hodgar, Digvijay S. (International Journal of Advances in Medicine, 2020)
Background: Diabetes is the commonest metabolic disorder affecting the people all over the world. Objective of the study was to identify the diastolic dysfunction in type 2 diabetes mellitus patient to recognize the early involvement of heart. Methods: This cross sectional study was conducted in tertiary care hospital cases of type II diabetes mellitus coming to our hospital and giving informed consent. Period of study was from September 2016 to February 2018. Consecutive type of non-probability sampling was used for the selection of study subjects. A total of 54 diagnosed patients of type II diabetes mellitus coming to our hospital and giving informed consent were included in the study. Results: Prevalence of diastolic dysfunction was observed to be 44.4% in patients of type 2 diabetes mellitus without cardiac manifestations. Prevalence of diastolic dysfunction was seen in 47.4% males in comparison to 42.9% females. Prevalence of diastolic dysfunction was 11.1%, 77.3% and 80% in cases with disease duration of 0-5 years, 6-10 years and more than 10 years respectively. Prevalence of diastolic dysfunction was more in cases with poor glycaemic control i.e. hemoglobin A1c (HbA1c) value >8% as compared to cases with good glycemic control. Conclusions: There was an association between the prevalence of diastolic dysfunction with the increasing age. We had higher percentage of patients with diastolic dysfunction as duration of diabetes increased. Diastolic dysfunction was seen in 55.2% patients receiving oral hypoglycaemic agents (OHAs) as compared to 23.5% patients who were on insulin and 50% patients who were on both insulin and OHAs.